Frontispiece: Size Matters: From Two‐Dimensional AuI–TlI Metallopolymers to Molecular Complexes by Simple Variation of the Steric Demand. Issue 15 (12th March 2019) - Seifert, Tim P.; Knoefel, Nicolai D.; Feuerstein, Thomas J.; Reiter, Kevin; Lebedkin, Sergei; Gamer, Michael T.; Boukis, Andreas C.; Weigend, Florian; Kappes, Manfred M.; Roesky, Peter W.
Abstract : Au‐Tl metallopolymers of different dimensionalities and heterobimetallic backbones were synthesized by using bis(acetylido)aurates(I) and thallium(I) trifluoromethylsulfonates. Their corresponding metal scaffolds are shown as a blue‐luminescent two‐dimensional framework (background), a one‐dimensional chain and a discrete cluster emitting in the yellow region of the visible spectrum (front). Furthermore, the luminescent samples are displayed under UV irradiation. For more information see Full Paper by P. W. Roesky et al. onpage 3799 ff.